Complementary coded thermal wave imaging scheme for thermal non-destructive testing and evaluation. Issue 1 (2nd January 2017) - Mulaveesala, Ravibabu; Arora, Vanita
Abstract: Infrared thermography is a well-established technique for the non-destructive characterisation of various materials. This technique relies on the analysis of acquired temperature profile over the test sample to evaluate the presence of surface and sub-surface anomalies within the material. Over past decade coded thermal excitation schemes and associated post processing (signal/video processing) schemes have gained vital attention in infrared thermographic community in various fields. However, in thermal non-destructive testing the usage of coded excitations are still relatively uncommon. This paper explores the feasibility of using complementary Golay coded excitation in active thermography. The newly developed technique is shown to be effective in increasing temporal signal to noise ratio by suppressing side lobes of the compressed pulse. The present experimental investigation emphasises the defect detection capabilities of Golay coded thermal wave imaging to characterise a carbon fibre reinforced plastic material having blind holes and inclusions as defects. An investigation of spatial signal to noise ratio is also presented.